2023
DOI: 10.1093/nsr/nwad120
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-controlled methanol conversion over zeolite catalysts

Abstract: The successful development and application in industry of Methanol-to-Olefins (MTO) process brought about an innovative and efficient route for olefin production via non-petrochemical resources and also attracted extreme attention of C1 chemistry and zeolite catalysis. Molecular sieve catalysts with diversified microenvironments embedding unique channel/cavity structure and acid properties, exhibit demonstrable features and advantages in shape-selective catalysis of MTO. Especially, the shape selective catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…15,16 The catalytic behavior of zeolites is determined by both acidity and pore confinement. 17,18 For MOR zeolite, the vast difference in the local confinement effect between 12-MR and 8-MR channels has been shown to tune the reaction in different ways, either in a positive or negative manner. 19 Taking the methanol/DME carbonylation reaction as an example, studies have shown that the carbonylation reaction would preferably take place on the Bro̷ nsted acid sites (BAS) within 8-MR pores.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The catalytic behavior of zeolites is determined by both acidity and pore confinement. 17,18 For MOR zeolite, the vast difference in the local confinement effect between 12-MR and 8-MR channels has been shown to tune the reaction in different ways, either in a positive or negative manner. 19 Taking the methanol/DME carbonylation reaction as an example, studies have shown that the carbonylation reaction would preferably take place on the Bro̷ nsted acid sites (BAS) within 8-MR pores.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of extracted coke by mass spectromery (MS) ,,, and the studies of the deactivation processes by different spectroscopic methods, such as UV–vis, Raman, ,, and 13 C nuclear magnetic resonance (NMR) spectroscopies, , revealed alkylated polycyclic aromatic hydrocarbons (PAHs) as the prevailing components of coke. ,, The compounds with up to ca. 4 condensed rings are proposed to reside in the micropores, , while higher aromatics are typically considered as the components of external coke, , although they could also deposit in the micropores. ,, The catalyst propensity to coking and the composition of coke are strongly dependent on the framework topology, which implies that the micropore confinement also governs the deposition of coke. ,, Nonetheless, the insights on how the micropore geometry affects the coke localization are very limited and mainly focused on ZSM-5 catalysts. Density functional theory analysis indicated that the coke molecules primarily deposit in the intersection of the 10 MR channels in ZSM-5 because of the highest stabilization provided by this largest void volume .…”
Section: Introductionmentioning
confidence: 99%
“…12,19,38 The catalyst propensity to coking and the composition of coke are strongly dependent on the framework topology, which implies that the micropore confinement also governs the deposition of coke. 4,6,42 Nonetheless, the insights on how the micropore geometry affects the coke localization are very limited and mainly focused on ZSM-5 catalysts. Density functional theory analysis indicated that the coke molecules primarily deposit in the intersection of the 10 MR channels in ZSM-5 because of the highest stabilization provided by this largest void volume.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect was a crucial factor contributing to their product shape selectivity. 13 Specifically, small-pore zeolites (8-membered rings) only allowed the passage of tiny molecules like ethylene and propylene, thus often serving as catalysts in the MTO process. 14–17 On the other hand, medium-pore zeolites (10-membered rings) permitted the passage of relatively larger diameter molecules, such as benzene, toluene, and xylene (BTX).…”
Section: Introductionmentioning
confidence: 99%